A Comparative Analysis of Reactive Müller Glia Gene Expression After Light Damage and microRNA-Depleted Müller Glia—Focus on microRNAs - Kang, Seoyoung; Larbi, Daniel; Andrade, Monica; Reardon, Sara; Reh, Thomas A.; Wohl, Stefanie G. (Frontiers in Cell and Developmental Biology, 2021)
Müller glia (MG) are the predominant glia in the neural retina and become reactive after injury or in disease. microRNAs (miRNAs) are translational repressors that regulate a variety of processes during development and are required for MG function. However, no data is available about the MG miRNAs in reactive gliosis. Therefore, in this study, we aimed to profile miRNAs and mRNAs in reactive MG 7 days after light damage. Light damage was performed for 8 hours at 10,000 lux; this leads to rapid neuronal loss and strong MG reactivity. miRNAs were profiled using the Nanostring platform, gene expression analysis was conducted via microarray. We compared the light damage dataset with the dataset of Dicer deleted MG in order to find similarities and differences. We found: 1) The vast majority of MG miRNAs declined in reactive MG 7 days after light damage. 2) Only four miRNAs increased after light damage, which included miR-124. 3) The top 10 genes found upregulated in reactive MG after light damage include Gfap, Serpina3n, Ednrb and Cxcl10. 4) The miRNA decrease in reactive MG 7 days after injury resembles the profile of Dicer-depleted MG after one month. 5) The comparison of both mRNA expression datasets (light damage and Dicer-cKO) showed 1502 genes were expressed under both conditions, with Maff, Egr2, Gadd45b, and Atf3 as top upregulated candidates. 5) The DIANA-TarBase v.8 miRNA:RNA interaction tool showed that three miRNAs were found to be present in all networks, i.e., after light damage, and in the combined data set; these were miR-125b-5p, let-7b and let-7c. Taken together, results show there is an overlap of gene regulatory events that occur in reactive MG after light damage (direct damage of neurons) and miRNA-depleted MG (Dicer-cKO), two very different paradigms. This suggests that MG miRNAs play an important role in a ubiquitous MG stress response and manipulating these miRNAs could be a first step to attenuate gliosis.